PTH-196 Chronic cholestasis and parenteral nutrition: prevalence and effect of bowel restoration surgery. (22nd June 2015) - Adaba, F; Iqbal, F; Vaizey, C; Gabe, S; Warusavitarne, J; Nightingale, J
Abstract : Introduction: Patients with mesenteric infarction can have intestinal failure due to a short bowel thereby needing parenteral nutrition. A short bowel and parenteral nutrition can increase the risk of chronic cholestasis. Restoring bowel continuity after a mesenteric infarction results in reduction or stopping parenteral nutrition requirements. The aims of this study are to determine the prevalence and the effect of restoring bowel continuity on chronic cholestasis. Method: A retrospective review of patients with a short bowel due to mesenteric infarction from 2000–2012. We defined chronic cholestasis as two of bilirubin, alkaline phosphatase and gamma-glutamyl transferase being 1.5 times the upper limit of normal for more than 6 months. Results: One hundred and four (55 females, median age 54 years) patients were identified. Seventy three (70%) patients had bowel continuity restored while 31 (30%) patients did not have bowel continuity restored. The prevalence of chronic cholestasis was 29%. Fifteen (21%) of 73 patients had chronic cholestasis. Following restoration of bowel continuity, 8 (53%) of 15 patients had a return of liver biochemistry to normal range within a year. Univariate analysis showed restoring bowel continuity (p = 0.002) was associated with a reduced risk of chronic cholestasis. Multivariate analysis showed cessation of PN was a significant factor in reducing chronic cholestasis (p = 0.02). Conclusion: The prevalence of chronic cholestasis is 29% for patients with a short bowel receiving parenteral nutrition. Chronic cholestasis resolves in over half patients after continuity is restored. Disclosure of interest: None Declared. References: Cavicchi M, Beau P, Crenn P, et al . Prevalence of liver disease and contributing factors in patients receiving home parenteral nutrition for permanent intestinal failure. Ann Intern Med . 2000;132(7):525–32 Lloyd DAJ, Zabron AA, Gabe SM. Chronic biochemical cholestasis in patients receiving home parenteral nutrition: prevalence and predisposing factors. Aliment Pharmacol Ther . 2008;27(7):552–60 Nightingale JM. Management of patients with a short bowel. World J Gastroenterol . 2001;7(6):741–51 Salvino R, Ghanta R, Seidner DL, et al . Liver failure is uncommon in adults receiving long-term parenteral nutrition. J Parenter Enter Nutr . 2006;30(3):202–8